NOVUM TESTAMENTUM A NOBIS VERSUM: THE ESSENCE OF ERASMUS’ EDITION OF THE NEW TESTAMENT - Jonge, Henk Jan de (The journal of theological studies, 1984)
HENK JAN DE JONGE; NOVUM TESTAMENTUM A NOBIS VERSUM: THE ESSENCE OF ERASMUS’ EDITION OF THE NEW TESTAMENT, The Journal of Theological Studies, Volume 35, Issue